Knowledge, attitude and risk behavior regarding HPV infection among senior students of Chiang Mai University - Thipsuda Krueyot; Tanawan Samleerat (Journal of Associated Medical Sciences, 2017)
Background: Human papillomavirus (HPV) is common sexually transmitted in Thailand. The incidence of HPV infection is currently increasing among adolescents and is likely to increase gradually. Senior students of the university are prompt to start a family or working. They should, therefore, have knowledge about prevention of HPV infection in order to reduce rate of HPV infection.